Enhanced Soil Decontamination via Electrokinetic Removal of Organic Pollutants - Ngieng, Hui Yee; Jusoh, Muhammad Noor Hazwan; Ahmad, Noraziah; Al Masud, Md Abdullah; Samaraweera, Hasara; Mohamed, Mohamed Mostafa (Tecno Scientifica Publishing, 2024)
Soil pollution is one of the concern issues in the Asia region. Soil acts as a shelter for underground microorganisms and provides nutrients for plants. Most of the organic contaminants are sourced from agriculture and industrial areas. Organic contaminants which are volatilized and immiscible lead to air and water pollution. Electrokinetic remediation is a technology that has been developed for soil remediation since a few decades ago. It is not fully developed and is still under investigation. Electrokinetic remediation is being applied to improve the removal efficiency of organic contaminants which exist in low hydraulic conductivity of soil or fine-grained soil. Generally, a low direct current, 1DCV/cm is applied. Facilitating agents including surfactant and co-solvent combined with electrokinetic remediation eliminated more organic contaminants compared with electrokinetic remediation alone. Electrokinetic remediation with the addition of bioremediation or phytoremediation process manipulates the transportation of organic contaminants in soil to increase the efficiency of remediation technologies. Electrokinetic remediation is recommended due to its flexibility, cost-effectiveness, and safety. One of the drawbacks is low effectiveness in removing non-polar organic pollutants due to weak desorption capacity and poor solubility in water. Co-solvents and surfactants can be introduced as alternatives to enhancing the solubility of non-polar pollutants and reducing surface tension, which improves their mobility within the soil matrix. These facilitating agents help improve the overall effectiveness of electrokinetic remediation, particularly for challenging contaminants.